Perancangan Environment Graphic Design (EGD) Pada Pasar Cihapit - Mochamad Dimas Alamsyah; Aldrian Agusta (Jurnal Riset Multidisiplin Edukasi, 2025)
Pasar Cihapit, located at Jl. Cihapit No.32, Bandung Wetan District, Bandung City, is renowned as a traditional market offering a variety of unique local culinary delights, attracting both locals and tourists. However, survey results indicate that the majority of visitors experience difficulties in finding information about the facilities in this market. This issue stems from the lack of effective graphic elements to provide directions and visual information. Based on interviews with vendors and visitors, they expressed the importance of having clear, easily accessible, and visually appealing information to enhance comfort. This study aims to evaluate and implement Environmental Graphic Design (EGD), such as signage, to assist visitors in identifying available facilities and services. The proper implementation of signage is expected to improve visitor mobility, provide more structured information, and create a more pleasant visiting experience. An integrated design approach is also anticipated to transform Pasar Cihapit into a more attractive, well-organized, and high-quality destination for the community.